Enhancement of the competitiveness and the financial capability of a manufacturing process through a new Value Stream Mapping approach, ISSN / e-ISSN 1746-6474 / 1746-6482 - Soltani Mohyiddine; Aouag Hichem; Mouss Mohamed Djamel (International Journal of Productivity and Quality Management, 2018)
The organisations having a futuristic look and aiming to impose their presence in the industrial field for a long possible term, are seeking for finding solutions linked to controlling their cash flow and assessing their competitiveness performances. Therefore, the purpose of this paper is to propose a new quality and cost value stream mapping for monitoring the costs consumption and assessing the competitiveness of a company. We use three key concepts namely life cycle costing for estimation of the most influential costs on the manufacturing process, the weighted DPMO and Sigma level for assessing the quality level and the competitiveness of the company. Finally, the data obtained are mapped using value stream mapping method for enabling the determination of dysfunctions in the cost and quality context.